IMF Survey, Volume 35, Issue 09. (IMF Survey; IMF Survey ;, 2006)
Funding the IMF; Middle East and Central Asia economic outlook; Is globalization a choice?; Latin American reform; Trade conference; Aid effectiveness; Long-term interest rates in G7 countries; Wage flexibility; Joint external debt website launched.